Inventarisasi Tumbuhan Obat di Hutan Lindung Kec. Ulu Pungkut, Kab. Mandailing Natal (Studi Kasus : Desa Alahankae, Hutanagodang, dan Simpang Banyak) - Ardiansyah Muda Lubis; Siti Latifah; Yunus Afifuddin (Peronema Forestry Science Journal, 2015)
The purpose of this research is to analyze species diversity and the use of  medicinal plants by the society aroud the protected forest Subdistrict Ulu Pungkut through species, how to use and part of  plants that use for medicine. The research was held at Alahankae, Hutanagodang, and Simpang Banyak villages, Mandailing Natal Regency, Nort Sumatera Province. The research used direct observation method by making sampling plot, literatur study, and identification of plants species. Inventory results in the field found 26 species of plants used as medicine. Most of medicinal plants that use by people was herb habitus. Leaves is the most part of medicinal plants that use by people for medicine. Eating is the general way of using medicinal plants. Cooking and grinding is the general threatment way before using the medicinal plants. Medicinal plants species diversity in protected forest area at Ulu Pungkut Subdistrict including moderate, aboundance of medicinal plant species classified as not much to rare, while the evenness index included to spread almost evenly.Keywords :  Inventory, Medicinal Plants, Reserve Forest, Bioiversity, Kecamatan Ulu Pungkut